UPAYA PEMAHAMAN PANTUN PADA MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN LAGU “RASA SAYANGE” - Rini Damayanti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This study describes the application of Rasa Sayange song music in improving students' understanding in learning Indonesian poetry. The research method uses qualitative descriptive. This research is based on problems in schools, especially students in third grade of Muhammadiyah Karangharjo Elementary School, who have difficulty in understanding rhymes and creating a rhymes in learning Indonesian. From this research, it can be concluded that the Music of Rasa Sayange Song is an effective method for increasing rhymes understanding for students in Indonesian subjects. The Rasa Sayange Music Method is the right method to arouse students' interest in learning, activating and creating students.